Physical and chemical oceanography during SONNE cruise SO277 from towed Video-CTD01, off Malta - Schmidt, Mark (PANGAEA, 2025)
Data set presents water column and bottom water oceanographic parameters recorded with a video-guided Water Sampler Rosette/CTD system during SO277 cruise off Malta (Berndt et al., 2021). The data set of VCTD01 was recorded on August 24th, 2020 and combines Seabird-CTD data with methane and CO2-sensor data and ship's navigation data (SeaPath, Kongsberg SP 320-5+). Data were recorded to localize fluid seepage at the seafloor east of Malta and Gozo.
Keywords: CTD; Mediterranean Sea; oceanography